2009
DOI: 10.1111/j.1751-7176.2009.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Glucose Metabolism and the Exaggerated Blood Pressure Response to Exercise Treadmill Testing in Normotensive Patients

Abstract: The authors aimed to investigate the association between glucose metabolism measures and the exaggerated blood pressure response (EXBPR) to exercise testing in normotensive nondiabetic patients. One hundred and forty‐two consecutive patients underwent office blood pressure (BP) measurements, 24‐hour BP monitoring, echocardiography, and treadmill exercise test according to the Bruce protocol. The population was divided into 2 groups according to EXBPR at a submaximal workload level. Furthermore, blood samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
2
13
1
Order By: Relevance
“…Furthermore, multivariate regression analysis revealed that a greater number of MS components was an independent determinant of high MAP during exercise after adjustment for potential confounders, including age and BMI. These findings are in agreement with previous published reports of significant associations with high lipoprotein cholesterol, 10,16 impaired glucose metabolism, 16,19 and MS 18 with exercise BP. In addition, the present results indicate that the accumulation of risk factors is also an important predictor of BP response to exercise.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, multivariate regression analysis revealed that a greater number of MS components was an independent determinant of high MAP during exercise after adjustment for potential confounders, including age and BMI. These findings are in agreement with previous published reports of significant associations with high lipoprotein cholesterol, 10,16 impaired glucose metabolism, 16,19 and MS 18 with exercise BP. In addition, the present results indicate that the accumulation of risk factors is also an important predictor of BP response to exercise.…”
Section: Discussionsupporting
confidence: 93%
“…Such an effect might have a greater influence on vascular reactivity than on basal tone. [16][17][18][19] Therefore, although resting BP may not necessarily be high when the vascular impairment is not yet very severe, the vascular reactivity may already be abnormal, possibly resulting in excessive BP elevation under stressful conditions, for example, during physical exertion.…”
Section: Introductionmentioning
confidence: 99%
“…A positive association has previously been observed between HOMA-IR score and BP response to exercise in nondiabetic adults with (39) and without (37) hypertension. Furthermore, BMI levels have been found to be related to exercise BP response in obese adolescents (8,9).…”
Section: Discussionmentioning
confidence: 62%
“…We focused on stimulated and basal NO release to assess endothelial function, large artery stiffness, and basal/peak exercise neurohormonal activation. It is possible, however, that other factors such endothelium‐derived hyperpolarizing factor, increased sympathetic outflow, asymmetric dimethyl arginine, and insulin levels may have contributed either collectively or in isolation to ExSBP and certainly this merits further investigation. Additionally, we considered only few of the possible mechanisms affecting both vascular and myocardial responsiveness to exercise.…”
Section: Discussionmentioning
confidence: 99%